Hysteroscopic‎ polypectomy with ‎endometrial resection for preventing recurrence of ‎endometrial polyps: A single-blinded randomized clinical ‎trial.‎ - Mansoureh Vahdat; Ashraf Sadat Mousavi; Mania Kaveh; Kambiz Sadegi; Hoda Abdolahi (Babol University of Medical Sciences, 2022)
Background: Recurrence of endometrial polyp following the hysteroscopic polypectomy is a significant concern for both the patients and physicians. This study aimed to evaluate the efficacy of combining hysteroscopic polypectomy with endometrial resection in reducing the rate of recurrence in women over 40 years old. Methods: In a single-blinded clinical trial, 94 women with endometrial polyps who were unwilling to future pregnancy were identified and randomly allocated to the intervention (hysteroscopic‎ polypectomy + endometrial resection) ‎and control group (hysteroscopic‎ polypectomy alone) group (n=47/each). Randomization was done using a simple randomization technique‎. The primary outcome measure was the polyp recurrence. The secondary outcome measure was the number of adverse events. Results: In total, polyp recurrence occurred in two (4.3%) patients of the intervention group and nine patients (19.1%) of the control group (P=0.019). All the recurrences occurred in the premenopausal patients (P=0.012). No adverse event was observed in any patients of both groups. Conclusion: Adding endometrial resection to hysteroscopic polypectomy, especially in postmenopausal women, is a safe method that significantly reduces the risk of recurrence of the endometrial polyp.